IMPLEMENTASI AKAD WAKALAH BIL UJRAH DALAM PELIMPAHAN WEWENANG PENYELENGGARAAN PERNIKAHAN PERSPEKTIF HUKUM EKONOMI SYARIAH (Studi Analisis Pada Shahira Islamic Wedding Organizer Surabaya) - akbar, mochammady el; mu'ammar, muhammad arfan (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2020)
Wakalah bil ujrah covenant implementation is an agreement covenant of an authority delegation to do something (delegating an affair) in which the implementation can be implemented in the field of wedding exertion by a wedding organizer. But generally, in the field implementation, the society has not been fully acknowledge and understanding how this implementation of an authority delegation in a wedding exertion accords with the the things which have been appointed by the syari’a economic law, and the legal consequences from the achieved wakalah agreement.The problems formulation of this thesis is how the form of the wakalah covenant implementation and also the system of the ujrah taking in the authority delegation of a wedding exertion by Shahira Wedding Organizer Surabaya and analyzing the implementation based on the syari’a economic law of the National Syari’a Board - Majelis Ulama Indonesia (DSN-MUI).This Study was conducted using online research instruments (online field research) with qualitative method. As for the data collecting techniques were done and achieved by online, observation, and the documentation data that are in correlate to the object of the study. The collected data, furthermore is arranged and analyzed using descriptive analysis method, it is describing how the akad wakalah bil ujrah implementation concept in obligating the authority the wedding exertion is done from the shahibbul hajat to Shahira Wedding Organizer Surabaya.The results of the research show that the wakalah bil ujrah covenant implementation in delegating the authority from the shahibbul hajat to Shahira Wedding Organizer Surabaya is done orally through the agreement in choosing the packages of Gumush, Altin, and Platin using simple statements (informal language) as the Surabaya’s people do. Furthermore it will be followed by some representation acts by the Shahira Wedding Organizer Surabaya. Dealing with the ujrah or the fee taking, it will be alocated and included into the price-list of the packages that automatically when it was on the first offer, the value of ujrah has been written and agreed. According to the perspective of the syari’a economic law, this wakalah bil ujrah practice done by the Shahira WO has fulfilled the well conformity in the implementation for the whole components between the both sides have been fulfilled in both of the pillars and the requirements that have been set by the Fatwa DSN-MUI No. 10/DSN-MUI/IV/2000 about wakalah.Keywords : Wakalah Bil Ujrah, Wedding Organizer and Syari’a Economic Law Perspective